A murine-ES like state facilitates transgenesis and homologous recombination in human pluripotent stem cells - Buecker, Christa (2010)
Murine embryonic stem cells have been shown to exist in two functionally distinct pluripotent states, embryonic stem cells (ES cell)- and epiblast stem cells (EpiSCs), which are defined by the culture growth factor conditions. Human ES cells appear to exist in an epiblast-like state, which in comparison to their murine counterparts, is relatively difficult to propagate and manipulate. As a result, gene targeting is difficult and to-date only a handful of human knock-in or knock-out cell lines exist. We explored whether an alternative stem cell state exists for human stem cells as well, and demonstrate that manipulation of the growth factor milieu allows the derivation of a novel human stem cell type that displays morphological, molecular and functional properties of murine ES cells and facilitates gene targeting. As such, the murine ES-like state provides a powerful tool for the generation of recombinant human pluripotent stem cell lines.